Perancangan Sistem Informasi Penitipan Hewan Peliharaan Pada RYOPETSHOP Berbasis Android - Prayogo, Lito; Siswanto, Agus; Rahim, Abdul (LPPM STIKOM Dinamika Bangsa, 2024)
This android-based pet hotel information system is essential for RYO PetShop in Jambi. As a pet hotel facility, the current system is still using manual book keeping and operates as a single-user system, resulting in less effective and efficient performance. The pet hotel owner must manage data manually, leading to a higher risk of recording errors or lost information. To address these issues, the pet hotel information system is developed using Java programming language and Firebase, employing the Waterfall method and the unified model language system approach, which includes Use Case diagrams, Activity Diagrams, and class diagrams.